Benznidazole Extended-Release tablets for improved treatment of chagas disease: Preclinical pharmacokinetic study - Davanço, Marcelo Gomes [UNESP]; Campos, Michel Leandro [UNESP]; Rosa, Talita Atanazio; Padilha, Elias Carvalho [UNESP]; Alzate, Alejandro Henao [UNESP]; Rolim, Larissa Araújo; Rolim-Neto, Pedro Josã; Peccinini, Rosângela Gonçalves [UNESP] (American Society for Microbiology, 2016)
Benznidazole (BNZ) is the first-line drug for the treatment of Chagas disease. The drug is available in the form of immediaterelease tablets for 100-mg (adult) and 12.5-mg (pediatric) doses. The drug is administered two or three times daily for 60 days. The high frequency of daily administrations and the long period of treatment are factors that significantly contribute to the abandonment of therapy, affecting therapeutic success. Accordingly, this study aimed to evaluate the preclinical pharmacokinetics of BNZ administered as extended-release tablets (200-mg dose) formulated with different types of polymers (hydroxypropyl methylcellulose K4M and K100M), compared to the tablets currently available. The studies were conducted with rabbits, and BNZ quantification was performed in plasma and urine by ultraperformance liquid chromatography methods previously validated. The bioavailability of BNZ was adequate in the administration of extended-release tablets; however, with the administration of the pediatric tablet, the bioavailability was lower than with other tablets, which showed that the clinical use of this formulation should be monitored. The pharmacokinetic parameters demonstrated that the extended-release tablets prolonged drug release from the pharmaceutical matrix and provided an increase in the maintenance of the drug concentration in vivo, which would allow the frequency of administration to be reduced. Thus, a relative bioavailability study in humans will be planned for implementation of a new product for the treatment of Chagas disease.